2023
DOI: 10.1186/s12870-023-04044-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of SPL gene family during flower morphogenesis and regulation in blueberry

Abstract: The SPL gene is a plant-specific transcription factor involved in the regulation of plant growth and development, which have been identified in woody plants. The process of floral bud differentiation affects the timing of flowering and fruit set and regulates plant growth, however, the mechanism of regulation of flower development by SPL genes is less studied. In this study, 56 VcSPL genes were identified in the tetraploid blueberry. The VcSPL gene family was classified into six subfamilies, and analysis of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
2
4
0
Order By: Relevance
“…In our study, we analyzed the tissue specific expression of EgSPLs from the available transcriptome data and the majority of EgSPL genes expressed in flower and shoot. Our results are consistent with the previous reports on expression of SPL genes in blue berry [56]. Our qPCR data on expression of 14 SPL genes that contain miR156 sites revealed confined expression of some SPL genes in male and female inflorescences.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we analyzed the tissue specific expression of EgSPLs from the available transcriptome data and the majority of EgSPL genes expressed in flower and shoot. Our results are consistent with the previous reports on expression of SPL genes in blue berry [56]. Our qPCR data on expression of 14 SPL genes that contain miR156 sites revealed confined expression of some SPL genes in male and female inflorescences.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we analyzed the tissue speci c expression of EgSPLs from the available transcriptome data and the majority of EgSPL genes expressed in ower and shoot. Our results are consistent with the previous reports on expression on SPL genes in blue berry [49]. Our qPCR data on expression of 14 SPL genes that contain miR156 sites, revealed that con ned expression of some SPL genes in male and female in orescences.…”
Section: Discussionsupporting
confidence: 93%
“…The sequence length (131–1076 aa) and MW (14.97 kDa -118.85 kDa) of SbSPL proteins varied greatly. This phenomenon was also observed in Vaccinium corymbosum VcSPLs (126–1072 aa; MW: 14.04–117.84 kDa) (Feng et al 2023b ), Prunus avium PavSPLs (162–1069 aa; MW: 18–118 kDa) (Sun et al 2023 ) and Nicotiana tabacum NtSPLs (119–1001 aa; MW: 13.7–111.3 kDa) (He et al 2023 ). SPL TFs diverged earlier than green algae (Guo et al 2008 ) and initially formed two distinct lineages (clade I and clade II) in land plants.…”
Section: Discussionmentioning
confidence: 69%